Development of Nutritious Sprinkles from Chicken Feet and Mung Beans for Pregnant Women at Risk of Chronic Energy Deficiency - Juliani, Kurnia Dwi; Hardinsyah, Hardinsyah; Palupi, Eny (Jurnal Gizi dan Pangan, 2023)
This research was aimed to develop the formulation of nutritious sprinkle made from chicken feet and mung beans and evaluate its nutritional and sensory quality. This pre-experimental study used a Completely Randomized Design (CRD). The sensory evaluation showed that most of the panelists accepted all formulations. The most preferred formulation based on the ranking test was F2 (chicken feet flour:mung bean flour of 2:1), which is suggested for use in energy-dense food. The water and protein content of the new formulation met the standard of supplementary food for pregnant women at risk of chronic energy deficiency. It is also claimed that the formulation can be used as a high protein and high calcium food.